Alkali delignification and Bacillus sp. BMP01 hydrolysis of rice straw for enhancing biofuel yields - Tsegaye, Bahiru (2021)
About 71.29% of lignin (maximum amount of lignin) was removed after 7% sodium hydroxide (NaOH) pretreatment followed by 3% pretreatment (about 67.13%). Also, maximum cellulose (about 71.33%) was preserved after 7% NaOH pretreatment. Results of reducing sugars obtained by spectrophotometric analysis (3,5-dinitrosalycilic acid method) of pretreated rice straw show about 88.27% conversion (753 mg/g) after the 13th day of hydrolysis by bacteria isolated from a termite. FE-SEM, XRD, FTIR, and TGA analyses show a significant amount of lignin was removed which helps in releasing cellulose tangled in lignin.